Evaluation of Medicare I: Administrative Issues - Eduardo T. Gonzalez; Corazon Urquico; Edwin Canonizado (Philippine Institute for Development Studies (PIDS), 1995)
Along with the economic evaluation of Medicare I, this paper looks into the designing of new policy and program options for the Medicare program. This will help to generate information necessary for developing new alternatives strategies in "coverage" pricing, in the context of organizational reform that aims for a more efficient utilization of resources.
Keywords: 330; medical care; insurance system; leverage; reserve capacity; financial liquidity; fund utilization; collection efficiency; return on investment (ROI)